2012
DOI: 10.1016/j.jacc.2012.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Early Anticoagulation of Bioprosthetic Aortic Valves in Older Patients

Abstract: Death and embolic events were relatively rare in the first 3 months after bioprosthetic aortic valve replacement. Compared with aspirin-only, aspirin plus warfarin was associated with a reduced risk of death and embolic events, but at the cost of an increased bleeding risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(37 citation statements)
references
References 17 publications
1
30
2
4
Order By: Relevance
“…Secondary outcomes included hemorrhaging stroke (ICD-9 codes 430–432), 18 death, and a composite endpoint comprised of thromboembolism, hemorrhagic stroke, or death to 3 years. Vital status was determined by the Medicare denominator file.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes included hemorrhaging stroke (ICD-9 codes 430–432), 18 death, and a composite endpoint comprised of thromboembolism, hemorrhagic stroke, or death to 3 years. Vital status was determined by the Medicare denominator file.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Brennan et al 7 demonstrated, through a retrospective cohort study with large sample size (25,656 patients), that this is the incidence of 1%/person-year for any of the aforementioned therapies.…”
Section: Resultsmentioning
confidence: 99%
“…A 2012 document comparing 25,656 patients post-SAVR showed an individual risk of stroke or bleeding event of 1% on aspirin monotherapy at 3 months. (51) The cohort placed on aspirin plus coumadin had a lower risk of embolic stroke but had a significantly higher risk of bleeding when compared to patients on aspirin monotherapy (relative risk of bleeding: 2.80, 95% CI: 2.18 to 3.60, p<0.0001).…”
Section: Anticoagulation and Bleeding In Savr And Tavi In The Elderlymentioning
confidence: 94%